2016
DOI: 10.1161/jaha.116.004160
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Regulates Krüppel‐Like Factor 5 Transcription Activity via Specificity Protein 1 S‐Sulfhydration at Cys664 to Prevent Myocardial Hypertrophy

Abstract: Background--Hydrogen sulfide (H 2 S) is a gasotransmitter that regulates multiple cardiovascular functions. Kr€ uppel-like factor 5 (KLF5) exerts diverse functions in the cardiovascular system. Whether and how H 2 S regulates KLF5 in myocardial hypertrophy is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…H 2 S attenuated myocardial hypertrophy induced by abdominal aortic constriction in rats, through connexin 43 up‐regulation (Huang et al , ). Our latest study confirmed that H 2 S regulated the transcription activities of Krüppel‐like factor 5 via sulfhydration of the transcription factor Sp1 at Cys664, to prevent myocardial hypertrophy (Meng et al , ). The exact mechanism(s) underlying the effects of H 2 S on cardiac hypertrophy in different models were not completely consistent.…”
Section: Introductionmentioning
confidence: 52%
“…H 2 S attenuated myocardial hypertrophy induced by abdominal aortic constriction in rats, through connexin 43 up‐regulation (Huang et al , ). Our latest study confirmed that H 2 S regulated the transcription activities of Krüppel‐like factor 5 via sulfhydration of the transcription factor Sp1 at Cys664, to prevent myocardial hypertrophy (Meng et al , ). The exact mechanism(s) underlying the effects of H 2 S on cardiac hypertrophy in different models were not completely consistent.…”
Section: Introductionmentioning
confidence: 52%
“…"H 2 S-Rich" and "H 2 S-Poor" Pathophysiological Conditions H 2 S has been implicated in the pathogenesis of multiple diseases, as overviewed in review articles. These range from cardiovascular diseases (e.g., myocardial reperfusion injury, cardiac hypertrophy, heart failure, atherosclerosis, hypertension) (Predmore et al, 2012b;Polhemus and Lefer, 2014;Ahmad et al, 2015;Meng et al, 2015aMeng et al, , 2016Shen et al, 2015;Wang et al, 2015a;Cao and Bian, 2016;Kanagy et al, 2017;Greaney et al, 2017) to various neurologic diseases (e.g., stroke, neuroinflammation) (Wang et al, 2014a;Bhatia, 2015;Kida and Ichinose, 2015;Wallace et al, 2015;Sen, 2017) and metabolic diseases (e.g., diabetes mellitus) (Desai et al, 2011;Szabo, 2012;Okamoto et al, 2015;Carter and Morton, 2016) to various forms of local and systemic inflammation (e.g., hemorrhagic shock, septic H 2 S Donors and H 2 S Biosynthesis Inhibitors shock, burn injury) (Wagner et al, 2009;Coletta and Szabo, 2013;McCook et al, 2014;Akter, 2016).…”
Section: H 2 S As An Endogenous Biologic Mediatormentioning
confidence: 99%
“…And GYY4137 enhanced S‐sulfhydration on SP‐1 if there was an overexpression of WT SP‐1 or SP‐1 had mutations of C659A, C689A and C692A but not C664A in cardiomyocytes. Moreover, GYY4137 failed to attenuate KLF5 promoter activity and mRNA expression, reduce the binding between SP‐1 and KLF5 promoter, decrease the mRNA expression of atrial natriuretic peptide and improve myocardial hypertrophy in angiotensin II‐induced cardiomyocytes if the SP‐1 mutation was C664A (Meng et al, ). These findings suggest that S‐sulfhydration at Cys 664 is essential for the inhibitory ability of KLF5 transcription and protective effect against myocardial hypertrophy induced by H 2 S.…”
Section: H2s Induced Protein S‐sulfhydrationmentioning
confidence: 99%
“…Previous research found that H 2 S has the potential to produce vasoconstriction or vasodilatation, angiogenesis, smooth muscle growth or apoptosis, cardioprotection and other effects (Mani et al, ; Tsikas and Cooper, ; Ping et al, ; Dunn et al, ; Katsouda et al, ; Marino et al, ). Our studies have suggested that H 2 S attenuates myocardial hypertrophy and fibrosis in spontaneously hypertensive rats (SHR) (Meng et al, ,c; Meng et al, ), inhibits atherosclerotic plaque formation and inflammation in the aorta of apolipoprotein E −/− mice fed a high fat diet (Liu et al, ), suppresses oxidative stress and apoptosis in myocardial ischaemia and reperfusion injury (Meng et al, ), augments mitochondrial function and the anti‐oxidative capacity of endothelial cells (Xie et al, ), and activates nuclear factor E2‐related factor 2 (Nrf2) to alleviate diabetes‐accelerated atherosclerosis both in vitro and in vivo (Xie et al, ). H 2 S also enhances the antioxidant activity, and regulates NO formation and kinase activity to maintain the homeostasis of the cardiovascular system (Liu et al, ; Chen et al, ; Shimizu et al, ; Cheng et al, ).…”
Section: Introductionmentioning
confidence: 99%